Laser Photobiomodulation and Antimicrobial Photodynamic Therapy in the Treatment of Ovine Otitis - Silva, Marcus Vinícius Alves da; Ferreira, Manoel Luiz; Michel, Ana Flávia Ribeiro Machado; Ribeiro, Thiago Santos; Souza, Vinícius de Oliveira Costa; Leite, Jacson Vale; da Silva, Guilherme Oliveira; Filho, Fernando Alzamora (Acta Scientiae Veterinariae, 2021)
Background: Otitis is a severe inflammation of the skin of the auditory canal which can impact animals of all ages. In sheep, this disease can occur in isolated cases or in the entire flock. Laser photobiomodulation can be used in combination with medication or as single therapy and the effects are analgesia, modulation of the inflammatory process, edema reduction, tissue restoration and stimulation of local microcirculation. Antimicrobial photodynamic therapy stands out as a promising alternative to antimicrobial drugs for the treatment of localized infections. This study aimed to report the use of laser phototherapies on a sheep with bacterial otitis. Case: A case of bacterial otitis in a 4-year-old sheep, Dorper, was treated at the Veterinary Hospital of the State University of Santa Cruz. In the anamnesis, the owner reported that the patient presented crusts in the auricular pavilions, and had been medicated with oxytetracycline 20%, administered intramuscularly, for two days and the crusts cleaned with iodine 10%, but the animal did not present clinical improvement. On physical examination, the animal presented constant head swaying, edema of the ears, otalgia, enlarged parotid lymph nodes and ear wounds. No ear discharge was observed, and the initial diagnosis was aural hematoma. The treatment prescribed was laser photobiomodulation for three consecutive days. The lesions were irradiated with a diode laser with a power of 0.1 W, irradiance of 3.5 W/cm2, continuous emission, spot area of 0.028 cm2, wavelength of 808 nm, energy of 4J/point, and fluency/point of 142.8J/cm2, with seven points on the external surface and four points on the internal surface of both ears. Two points were also targeted on the parotid lymph nodes with infrared laser (λ = 808 nm), with energy of 2J/point. On the fourth day of hospitalization, there was a reduction in lesions, decreased edema and absence of pain and on the sixth day of hospitalization, the patient presented mucopurulent otorrhea. The material from the auricular pavilions was collected for cytological examination, confirming the clinical diagnosis of bacterial otitis. Two sessions of Antimicrobial Photodynamic Therapy (aPDT) were performed with an interval of 48 hours, with application of 0.01 % methylene blue, pre-irradiation time of five minutes and irradiation with diode laser with a power of 0.1 W, 660 nm wavelength and 9J/point energy. On the 10 th day after the start of the treatment, there was no pain, healing of ear wounds, and no otorrhea. An additional photobiomodulation session was performed on the unhealed wounds in the auditory canal with red laser (λ = 660nm), on 5 points with an energy of 1J/point. On the 15th day, the left ear was healed and the right ear presented otorrhea, and a further session of aPDT was performed. On the 17th day after starting treatment there was no secretion and all lesions were healed. The patient was subsequently monitored for one month, showing no change or relapse. Discussion: Laser photobiomodulation treatment and antimicrobial photodynamic therapy were efficient in treating bacterial otitis without the use of antibiotics, promoting clinical improvement and patient well-being, making it an alternative to conventional treatment. After searches on the Pubmed, Scielo and Escopus databases using photobiomodulation and antimicrobial photodynamic therapy in sheep otitis as descriptors, this is believed to be the first report on the use of laser phototherapy in sheep otitis. Further studies are needed to establish the dosimetry and frequency of the sessions, as, besides considering animal well-being, this species is an excellent model for human experimentation.